Application Of The Technology Acceptance Model (Tam) In Testing Consumer Behavioral Intentions On The Use Of The Brighton "Digispace" Application - Yulistina Yulistina; Agus Fredy Maradona (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to analyze the application of the Technology Acceptance Model (TAM) in testing consumer behavioral intentions when using the Brighton "Digispace" application. This research will be carried out at Brighton Real Estate. The reason researchers conducted research on Brighton Real Estate was because there were indications of the attitudes of Brighton Digispace application users who felt dissatisfied with the application. The sample for this research was 145 respondents who were Brighton Real Estate customers who bought or rented property in the Bali area. Data was collected using the questionnaire method and analyzed using the Partial Least Square (PLS) test. The results of the PLS analysis show that Perception of perceived ease of use has a positive and significant effect on attitude toward usage, Perception of perceived usefulness has a positive and significant effect on attitude toward usage, Perception of perceived usefulness , Social influence, Online experience has a positive and significant effect on behavior intention to use, Perceived attitude toward and Perceived ease of use do not have a positive and significant effect on behavior intention to use, Social influence has a positive and significant effect on perceived ease of use, Social influence does not have a positive and significant effect on perceived usefulness, Knowledge about product has a positive and significant effect on perceived usefulness, Knowledge about product and Online experience has a positive and significant effect on perceived ease of use.